Signature of a tropical Pacific cyclone in the composition of the upper troposphere over Socorro, NM. Issue 21 (11th November 2015) - Minschwaner, K.; Manney, G. L.; Petropavlovskikh, I.; Torres, L. A.; Lawrence, Z. D.; Sutherland, B.; Thompson, A. M.; Johnson, B. J.; Butterfield, Z.; Dubey, M. K.; Froidevaux, L.; Lambert, A.; et al.
Abstract: We present a case study based on balloon‐borne ozone measurements during the SouthEast American Consortium for Intensive Ozonesonde Network Study in August–September 2013. Data from Socorro, NM (34°N, 107°W) show a layer of anomalously low ozone in the upper troposphere (UT) during 8–14 August. Back trajectories, UT jet analyses, and data from the Microwave Limb Sounder (MLS) on the Aura satellite indicate that this feature originated from the marine boundary layer in the eastern/central tropical Pacific, where several disturbances and one hurricane (Henriette) formed within an active region of the Intertropical Convergence Zone in early August 2013. The hurricane and nearby convection pumped boundary layer air with low ozone (20–30 ppbv) into the UT. This outflow was advected to North America 3–5 days later by a strong subtropical jet, forming a tongue of low ozone observed in MLS fields and a corresponding layer of low ozone in Socorro vertical profiles. Key Points: Impacts of a tropical cyclone are seen in tropospheric ozone at midlatitudes